Response of selected crop associations to groundwater table depth in an inland valley - Carsky, R.J.; Walker, P.; Hauser, S.; Dashiell, Kenton E.; Dixon, A. (Elsevier, 1993)
The success of inland valley crop production in humid and subhumid areas of subSaharan Africa depends on the availability of appropriate crop varieties with some tolerance to excess moisture. Performance of upland crop associations [cassava (Manihot esculenta) + sweet potato (Ipomoea batatas) and cassava + soybean (Glycine max)] was observed in a trial conducted along a small valley toposequence. Groundwater table depth (GWT) was a significant covariate for cassava yield and regression analysis showed that cassava clones of similar yield potential responded similarly and positively to increasing GWT depth (r2=0.77) regardless of associated crop. Sweet potato tuber production was related to GWT depth for variety TIS 9465 (r2=0.47) but not for TIS 8441. Sweet potato was more tolerant of shallow GWT than cassava. Combined cassava and sweet potato tuber production was also positively correlated to GWT depth (r2=0.83). The range of GWT depth to be considered by plant breeders screening cassava and sweet potato varieties for excess moisture in inland valleys should include depths 0.2 to 0.4 m, because those depths were shown to be stressful to these crops.